Merekonstruksi Sejarah SUB Komandemen Sumatera Selatan - Ravico Ravico (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2020)
Local history is often underestimated, so many primary sources of history are neglected and damaged. Therefore, the need for the existence of the museum as a container for the preservation of historical sites. For example, the Museum Subkoss Garuda Sriwijaya, which stores objects of community struggle in Southern Sumatera against the Dutch Colonial. However, lack of interest and information so that many collections in the museum are considered as insignificant data. Therefore, the need to reconstruct the history behind the museum collection as a first step. This research uses historical research methods with steps, namely; heuristics, verification, interpretation and historiography. To analyze the data obtained, the archeological approach is used to study historical heritage objects to find the facts behind the objects. The results of this study confirm that this museum building has a long historical value from its function as a government office during the Dutch and Japanese colonial periods and was once a sub -oss headquarters. In the fight against invaders, there are some relics such as the C3082 steam locomotive, Jeep Willys STD 156 car, flat cannon and landmijn. All of these objects have a long history of maintaining independence. Keywords : Museum, History and Subkoss